Assessment of DNA methylation status in early stages of breast cancer development - van Hoesel, A Q (Nature Publishing Group, 2013)
BACKGROUND: Molecular pathways determining the malignant potential of premalignant breast lesions remain unknown. In this study, alterations in DNA methylation levels were monitored during benign, premalignant and malignant stages of ductal breast cancer development. METHODS: To study epigenetic events during breast cancer development, four genomic biomarkers (Methylated-IN-Tumour (MINT)17, MINT31, RARβ2 and RASSF1A) shown to represent DNA hypermethylation in tumours were selected. Laser capture microdissection was employed to isolate DNA from breast lesions, including normal breast epithelia (n=52), ductal hyperplasia (n=23), atypical ductal hyperplasia (n=31), ductal carcinoma in situ (DCIS, n=95) and AJCC stage I invasive ductal carcinoma (IDC, n=34). Methylation Index (MI) for each biomarker was calculated based on methylated and unmethylated copy numbers measured by Absolute Quantitative Assessment Of Methylated Alleles (AQAMA). Trends in MI by developmental stage were analysed. RESULTS: Methylation levels increased significantly during the progressive stages of breast cancer development; P-values are 0.0012, 0.0003, 0.012, <0.0001 and <0.0001 for MINT17, MINT31, RARβ2, RASSF1A and combined biomarkers, respectively. In both DCIS and IDC, hypermethylation was associated with unfavourable characteristics. CONCLUSION: DNA hypermethylation of selected biomarkers occurs early in breast cancer development, and may present a predictor of malignant potential.